Incidence of microvascular dysfunction is increased in hyperlipidemic mice, reducing cerebral blood flow and impairing remote memory - Hernandez Torres, Luis Daniel; Rezende, Flavia; Peschke, Eva; Will, Olga; Hövener, Jan-Bernd; Spiecker, Frauke; Özorhan, Ümit; Lampe, Josephine; Stölting, Ines; Aherrahrou, Zouhair; Künne, Carsten; Kusche-Vihrog, Kristina; et al. (Frontiers in Endocrinology, 2024)
The development of cognitive dysfunction is not necessarily associated with diet-induced obesity. We hypothesized that cognitive dysfunction might require additional vascular damage, for example, in atherosclerotic mice. We induced atherosclerosis in male C57BL/6N mice by injecting AAV-PCSK9DY (2x1011 VG) and feeding them a cholesterol-rich Western diet. After 3 months, mice were examined for cognition using Barnes maze procedure and for cerebral blood flow. Cerebral vascular morphology was examined by immune¬histology. In AAV-PCSK9DY-treated mice, plaque burden, plasma cholesterol, and triglycerides are elevated. RNAseq analyses followed by KEGG annotation show increased expression of genes linked to inflammatory processes in the aortas of these mice. In AAV-PCSK9DY-treated mice learning was delayed and long-term memory impaired. Blood flow was reduced in the cingulate cortex (-17%), caudate putamen (-15%), and hippocampus (-10%). Immunohistological studies also show an increased incidence of string vessels and pericytes (CD31/Col IV staining) in the hippocampus accompanied by patchy blood-brain barrier leaks (IgG staining) and increased macrophage infiltrations (CD68 staining). We conclude that the hyperlipidemic PCSK9DY mouse model can serve as an appropriate approach to induce microvascular dysfunction that leads to reduced blood flow in the hippocampus, which could explain the cognitive dysfunction in these mice.